The Implementation of Augmented Reality in Science Education in Secondary Schools - Putri, Dinda Febrianti; Baharun, Hasan (International Journal of Instructional Technology, 2023)
This study aims to explore the implementation of Augmented Reality (AR) in science education in secondary schools and its impact on students' motivation and understanding of the material. The research employs a qualitative approach to examine how AR technology is utilized in science classrooms and how it affects student engagement and learning outcomes. Data were collected through interviews with science teachers and students, as well as observations of AR implementation in the classroom. The findings indicate that the use of AR significantly enhances the conceptual visualization of science content, improves interactivity, and deepens students' understanding. Additionally, the technology motivates students to engage more actively in learning and increases their interest in the subject. This study contributes to educational literature by demonstrating how AR technology can be effectively applied to create more engaging and relevant learning experiences in secondary schools.